Students’ Perception in Learning Narrative Text Using Animated Videos - Rahmawati, Nisa; Siswana (FKIP Unismuh Makassar, 2025)
This study was motivated by the issue of students' low comprehension of narrative texts in English language learning, which is considered to be caused by the use of conventional learning media that are uninteresting and unsuitable for students' learning styles. Therefore, this study aims to explore and analyze students' perceptions of the use of alternative learning media, particularly animated videos, in improving their comprehension of narrative texts.The purpose of this study is to explore learners' perceptions of the use of animated videos as a medium for learning narrative text, as well as to identify the benefits and technical obstacles that arise during the learning process. This study used descriptive qualitative method with data collection techniques in the form of semi-structured interviews conducted with ten learners in one of the high schools in East Jakarta, with data analysis carried out thematically through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the application of animated videos was able to increase learning motivation, interest in the material, and students' understanding of the structural elements of narrative text such as plot, character, and setting. In addition, the media also contributed to the improvement of English language skills, especially in the aspects of listening and speaking. However, some students faced technical obstacles, such as narration that was too fast and accents that were difficult to understand. This study contributes to the development of adaptive, engaging, and diverse learning styles-appropriate animated video-based English language learning, and provides empirical insights for future innovations in learning media.